A Study for Tooth Bleaching via Carbamide Peroxide-Loaded Hollow Calcium Phosphate Spheres - Tao Qin; Torbjörn Mellgren; Steven Jefferies; Wei Xia; Håkan Engqvist (MDPI AG, 2016)
The objective of this study was to investigate if a prolonged bleaching effect of carbamide peroxide-loaded hollow calcium phosphate spheres (HCPS) can be achieved. HCPS was synthesized via a hydrothermal reaction method. Carbamide peroxide (CP) was-loaded into HCPS by mixing with distilled water as solvent. We developed two bleaching gels containing CP-loaded HCPS: one gel with low HP concentration as at-home bleaching gel, and one with high HP concentration as in-office gel. Their bleaching effects on stained human permanent posterior teeth were investigated by measuring the color difference before and after bleaching. The effect of gels on rhodamine B degradation was also studied. To investigate the potential effect of remineralization of using HCPS, bleached teeth were soaked in phosphate buffer solution (PBS) containing calcium and magnesium ions. Both bleaching gels had a prolonged whitening effect, and showed a strong ability to degrade rhodamine B. After soaking in PBS for 3 days, remineralization was observed at the sites where HCPS attached to the teeth surface. CP-loaded HCPS could prolong the HP release behavior and improve the bleaching effect. HCPS was effective in increasing the whitening effect of carbamide peroxide and improving remineralization after bleaching process.